Re-evaluation of histological findings after colocystoplasty and gastrocystoplasty. Issue 6 (December 2019) - Kardos, Daniel J.; Kereskai, Laszlo; Tornoczky, Tamas; Farkas, Kornelia; Davidovics, Anna; Farkas, Andrew; Vastyan, Attila M.; Pinter, Andrew B.; Vajda, Peter
Summary: Introduction: The potential of malignant transformation and its risk factors after bladder augmentation performed in childhood are still unknown. The necessity of surveillance cystoscopies and biopsies has been questioned in the past decade. Objective: In a previous study, the authors did not detect any malignancy after colocystoplasty (CCP) or gastrocystoplasty (GCP) during the short-term follow-up, however, various alterations of the mucosa were found. A correlation between the nature of histological changes and the frequency of bacterial colonization after CCP were also found. The authors hypothesized that a longer-term follow-up of their patients would reveal an increase in pathological change or show stronger association between the histological alteration, bacterial colonization, and/or stone formation. Patients and methods: Thirty-five patients (20 cases of colocystoplasties – CCPs; 15 cases of gastrocystoplasties – GCPs) participated in the study published in 2002. All patients were followed biannually with endoscopic assessment and biopsies. Two independent pathologists, evaluated regular biopsies from the native bladder, from the segment used for augmentation and from the anastomosis line. Etiology, frequency of positive urine cultures, and stone events were recorded and compared with histological findings between groups and with the previously published results. Results: Continuous surveillance allowed the follow-up of 30 patients (CCP 19/20, GCP 11/15) for 20 and 15 years. No malignancies were identified. Results of biopsies showed significant difference between groups (summarized in the tables). Chronic inflammatory changes were found following both types of augmentations, but they were more common in the urothelium following GCP and more common in the colonic mucosa following CCP. The rate of metaplastic lesions was higher after gastrocystoplasty (GCP). Significant association was found between the etiologic factor and the nature of histological change after CCP, as metaplastic lesions occurred only in patients with bladder exstrophy. Stones occurred more frequently in exstrophy patients as well. The nature of the histological changes did not correlate with positive urine cultures in either of the groups. Significantly higher incidence of bacterial colonization and stone occurrence were found after CCP. Conclusions: Long-term follow-up of the patients failed to reveal an increase in pathological changes, and no malignancies were observed. According to the results of this study, etiology of bladder dysfunction and the type of augmentation might influence the histological alterations after augmentation cystoplasty. The efficiency of surveillance cystoscopies and biopsies are low. The present data suggest that surveillance cystoscopy and biopsy should not be routinely performed, and should be done only if the symptoms are suspicious for malignancy. Summary Table CCP Urothelium ( n  = 55) Anastomosis ( n  = 55) Bowel mucosa ( n  = 55) Normal 33 (60%) 28 (51%) 17 (31%) Inflammation 19 (34%) 23 (42%) 38 (69%) Metaplasia 3 (6%) 4 (7%) 0 GCP Urothelium ( n  = 36) Anastomosis ( n  = 36) Gastric mucosa ( n  = 36) Normal 10 (28%) 15 (42%) 27 (75%) Inflammation 20 (55%) 16 (44%) 9 (25%) Metaplasia 6 (17%) 5 (14%) 0